Dietary supplementation with rice bran or navy bean alters gut bacterial metabolism in colorectal cancer survivors. Issue 1 (12th September 2016) - Sheflin, Amy M.; Borresen, Erica C.; Kirkwood, Jay S.; Boot, Claudia M.; Whitney, Alyssa K.; Lu, Shen; Brown, Regina J.; Broeckling, Corey D.; Ryan, Elizabeth P.; Weir, Tiffany L.
Abstract : Twenty‐nine colorectal cancer survivors ate a meal and snack daily for 28 days that were supplemented with rice bran or navy bean powder, or consumed a non‐supplemented macronutrient matched control. The microbial genes that break down plant cell wall fibers were increased by rice bran consumption, alongside microbial metabolite byproducts that may reduce inflammation and regulate appetite. In addition, the number of gut bacterial species increased with both rice bran and navy bean powder by day 28. Our research suggests that rice bran should be investigated further for colorectal cancer chemopreventive effects. Abstract : Scope: Heat‐stabilized rice bran (SRB) and cooked navy bean powder (NBP) contain a variety of phytochemicals that are fermented by colonic microbiota and may influence intestinal health. Dietary interventions with these foods should be explored for modulating colorectal cancer risk. Methods and results: A randomized‐controlled pilot clinical trial investigated the effects of eating SRB (30 g/day) or cooked navy bean powder (35 g/day) on gut microbiota and metabolites (NCT01929122). Twenty‐nine overweight/obese volunteers with a prior history of colorectal cancer consumed a study‐provided meal and snack daily for 28 days. Volunteers receiving SRB or NBP showed increased gut bacterial diversity and altered gut microbial composition at 28 days compared to baseline. Supplementation with SRB or NBP increased total dietary fiber intake similarly, yet only rice bran intake led to a decreased Firmicutes:Bacteroidetes ratio and increased SCFA (propionate and acetate) in stool after 14 days but not at 28 days. Conclusion: These findings support modulation of gut microbiota and fermentation byproducts by SRB and suggest that foods with similar ability to increase dietary fiber intake may not have equal effects on gut microbiota and microbial metabolism.